A rank-one convex, nonpolyconvex isotropic function on $GL^{\!+}(2)$ with compact connected sublevel sets. Issue 2 (April 2022) - Voss, Jendrik; Ghiba, Ionel-Dumitrel; Martin, Robert J.; Neff, Patrizio
Abstract : According to a 2002 theorem by Cardaliaguet and Tahraoui, an isotropic, compact and connected subset of the group $GL^{\!+}(2)$ of invertible $2× 2$ - - matrices is rank-one convex if and only if it is polyconvex. In a 2005 Journal of Convex Analysis article by Alexander Mielke, it has been conjectured that the equivalence of rank-one convexity and polyconvexity holds for isotropic functions on $GL^{\!+}(2)$ as well, provided their sublevel sets satisfy the corresponding requirements. We negatively answer this conjecture by giving an explicit example of a function $W\colon GL^{\!+}(2)→ \mathbb {R}$ which is not polyconvex, but rank-one convex as well as isotropic with compact and connected sublevel sets.